Quota Admission Policies and Students’ Retention in Colleges of Education in North-West Zone, Nigeria - Hiliya, Abubakar Abbas (EDUMALSYS Journal of Research in Education Management, 2024)
This study examined quota admission policies and students’ retention in Colleges of Education in North-west Zone, Nigeria. The study was guided by two research questions, two research objectives and one research hypothesis. The study employed a descriptive survey research design of correlational type. The population of the study were drawn from states-owned Colleges of Educations in North-west Zone, Nigeria which comprised of Admission Officers and students numbering 40372. A total of seven admission officers, 378 students were selected for the study guided by Research advisor, (2006). Purposive and proportionate sampling techniques were used. Two sets of researcher’s designed instruments were used such as Admission Policy Questionnaire (APQ) and Students’ Retention Scale (SRS). These instruments were validated by research experts using face, content and construct validity. Reliability indices of 0.78 and 0.85 were realized after subjecting the instruments for trial testing. Hypothesis was tested at 0.05 level of significance using Pearson Product Moment Correlation Coefficient. Finding of the study, indicated that there was no significant correlation between the variables. The study concluded that admission policies based on merit, catchment area and educationally less-developed states (quota admission) and students’ retention may not depend on each other. This is because student could be admitted based on the criteria of merit but perform abysmally and eventually drop out of the programme and student could be admitted based on catchment area or educationally less developed states criteria eventually perform academically well (good grade performance) after entering college due to factors such as family support, normative congruence, serious concentration on studies, regularity and punctuality. Study recommended that admission seekers should thoroughly be investigated with a view of offering them matching courses to their prior secondary schools, and merit based admission policy be given much priority than catchment and educationally less developed states policy.